An Empirical Approach for Validation of Inter-Rater Reliability of Identified Candidate Aspects - Aravindan, JS; Vivekanandan, K (International Journal of Computer Sciences and Engineering, 2025)
The development of technologies for observing the relevancy of identified candidate aspects of the products and validating the reliability of filed experts is a challenging process. If the identified candidate aspects is taken into consideration for decision making process, the technology has to meet certain feasibility criteria like acceptance of aspects by product experts (Judges). Questionnaires with extracted aspects were distributed to Judges and the candidate aspects are identified. This paper describes the content validity evaluation of identified candidate aspects. The validity of the instrument was evaluated by two field experts who were asked to score each aspect on a 4-point Likert scale (1. Not Relevant, 2. Item need some revision, 3. Relevant but need minor revision, 4. Very Relevant) on relevance of 5 product (Apex AD2600 Progressive-scan DVD player, Canon G3, Creative Labs Nomad Jukebox Zen Xtra 40GB, Nikon Coolpix 4300 and Nokia 6610) datasets and the Kappa Score is calculated.